The cascading pathogenic consequences of Sarcoptes scabiei infection that manifest in host disease. Issue 4 (18th April 2018) - Martin, Alynn M.; Fraser, Tamieka A.; Lesku, John A.; Simpson, Kellie; Roberts, Georgia L.; Garvey, Jillian; Polkinghorne, Adam; Burridge, Christopher P.; Carver, Scott
Abstract : Sarcoptic mange, caused by the parasitic mite Sarcoptes scabiei, causes a substantive burden of disease to humans, domestic animals and wildlife, globally. There are many effects of S. scabiei infection, culminating in the disease which hosts suffer. However, major knowledge gaps remain on the pathogenic impacts of this infection. Here, we focus on the bare-nosed wombat host ( Vombatus ursinus ) to investigate the effects of mange on: (i) host heat loss and thermoregulation, (ii) field metabolic rates, (iii) foraging and resting behaviour across full circadian cycles, and (iv) fatty acid composition in host adipose, bone marrow, brain and muscle tissues. Our findings indicate that mange-infected V. ursinus lose more heat to the environment from alopecia-affected body regions than healthy individuals. Additionally, mange-infected individuals have higher metabolic rates in the wild. However, these metabolic demands are difficult to meet, because infected individuals spend less time foraging and more time inactive relative to their healthy counterparts, despite being outside of the burrow for longer. Lastly, mange infection results in altered fatty acid composition in adipose tissue, with increased amounts of omega-6 acids, and decreased amounts of omega-3 acids, a consequence of chronic cutaneous inflammation and inhibition of anti-inflammatory responses. These findings highlight the interactions of mange-induced physiological and behavioural changes, and have implications for the treatment and rehabilitation of infected individuals.